Eco-Friendly Solutions to Heavy Metal Pollution: The Role of Microbial Bioremediation — A Mini Review (Journal of Environmental Bioremediation and Toxicology, 2025)
The accumulation of heavy metals in the environment is a grave threat and is the result of mining, agricultural, and industrial activities. This review article examines eco-friendly processes, including microbial bioremediation, to mitigate heavy metal contamination. Heavy metals have been present in the environment since the beginning of time. Their concentrations are rising due to anthropogenic factors and are contributing to several neurological, cardiovascular, and renal diseases, highlighting the urgency for effective remediation techniques. Microbial bioremediation utilizes the inherent capabilities of microorganisms to detoxify heavy metals through various processes such as bioaccumulation, biosorption, and biotransformation. These processes immobilize or convert heavy metals into less toxic forms. It offers a sustainable alternative to conventional chemical and physical remediation techniques, which are costly and often result in the production of harmful byproducts. This review discusses the complex processes involved in microbial bioremediation, the types of microorganisms used, and the relative benefits of microbial bioremediation over traditional techniques. Furthermore, biotechnological advances such as genetic engineering and the formation of microbial consortia, which improve the effectiveness of bioremediation initiatives, are also discussed. Despite the potential of microbial solutions, several issues exist that necessitate further investigation into the integration of recent advancements and modern applications to enhance the efficacy and efficiency of bioremediation methods, ultimately prioritizing environmental sustainability.
Keywords: Microbial bioremediation; Heavy metals; Pollution; Microbes; Eco-friendly approach